No detrimental effect of Bt maize pollen containing Cry1Ab/2Aj or Cry1Ac on adult green lacewings Chrysoperla sinica Tjeder - Yan-min LIU; Yun-he LI; Xiu-ping CHEN; Xin-yuan SONG; Ping SHEN; Yu-fa PENG (Journal of Integrative Agriculture, 2019)
Adult Chrysoperla sinica Tjeder is a common pollen feeder in maize fields. They are thus directly exposed to insecticidal proteins by consumption of genetically engineered maize pollen containing Bacillus thuringiensis (Bt) proteins. Here we assessed the potential effects of Cry1Ab/2Aj- or Cry1Ac-containing Bt maize pollen on the fitness of adult C. sinica via a dietary-exposure assay under laboratory conditions. Survival, pre-oviposition, fecundity and adult dry weight did not differ between adult C. sinica consuming Bt or the corresponding non-Bt maize pollen. The stability of the Cry protein in the food sources and uptake of the Cry protein by adult C. sinica during the feeding experiment were confirmed by ELISA. These results demonstrate that adult C. sinica are not affected by the consumption of Cry1Ab/2Aj- or Cry1Ac-containing maize pollen, suggesting that production of Bt maize expressing cry1Ab/2Aj or cry1Ac genes will pose a negligible risk to adult C. sinica.